Penggunaan Media Gambar Dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas III Di SDN 2 Buwun Mas - Isnawati, Mila; Sudrajat, Husaen; Ardhi, Shohibul (Journal of Teaching and Elementary Education, 2025)
Research with the title: "Use of Image Media in Improving Mathematics Learning Outcomes for Class III Students at SDN 2 Buwun Mas Belongas Academic Year 2022/2023". aims to determine the increase in mathematics learning outcomes after using image media in class III students at SDN 2 Buwun Mas Belongas. This research uses a qualitative approach. The nature of this research is descriptive. Data collection was carried out using interview and documentation techniques. Meanwhile, for data analysis techniques, researchers use data reduction, data presentation and drawing conclusions. The results of the research through analysis show that the use of image media in mathematics subjects for Class III Students at SDN 2 Buwun Mas Belongas, Sekotong District has been carried out quite well. This can be seen based on interviews conducted by researchers, namely the selection of image media made by class III teachers according to the material and students' level of development. Considering the characteristics of class III students, the learning process still requires an intermediary who can describe abstract things into concrete forms, namely those that can be captured by the five senses so that students can easily understand the concepts taught by the teacher. So choosing interesting media will have a big influence on the learning process. The consideration for using image media in mathematics learning is to facilitate students' understanding. Apart from that, image media can also clarify lesson material so that it is easy to observe. Image media can also generate interest in students. Lastly, image media is used to abbreviate a description or material which, if explained in words, might require a long description.